Enhancing Entrepreneurial Competencies and Student Engagement through Gamification in Learning Management Systems - Rachmadi, Pratiwi; Situmorang, Robinson; Sukardjo, Moch.; Indrajit, Richardus Eko; Gautama, Elliana (Aptisi Transactions On Technopreneurship (ATT), 2025)
This study addresses the growing need for innovative strategies to enhance student engagement in digital learning environments by investigating the effects of gamification on student motivation and academic performance within Learning Management Systems (LMS). Despite its increasing adoption, the long-term impact of gamification on learning outcomes remains underexplored, particularly in structured educational settings. Using an experimental design, students were divided into two groups: the experimental group, which used a gamified LMS, and the control group, which used a traditional LMS. Results indicated that the experimental group exhibited significantly higher engagement levels (85%) compared to the control group (62%) and spent, on average, 30% more time on the LMS. Participation in optional activities was 40% higher in the gamified group. Motivation analysis revealed increased intrinsic motivation (72%) and extrinsic motivation (78%) among the experimental group, supported by features such as points and badges. Academic performance improvements were also evident, with the experimental group achieving 10% higher final exam scores and a 15% higher assignment completion rate. While findings suggest that gamification enhances student engagement and learning outcomes, feedback on competitive elements like leaderboards highlights the need for careful design considerations to balance motivation and inclusivity. This study provides empirical insights into the effectiveness of gamification as a scalable and adaptive strategy for enhancing digital education, informing future developments in educational technology.